Attitude of Nursing Students towards Computer Assisted Learning in a Selected Nursing College, Hafar al Batin, Saudi Arabia - Selwa Y Abdeldafie, Bindu Kaipparettu Abraham (International Journal of Innovative Research in Medical Science, 2017)
Computer knowledge and skills are becoming essential components technology in nursing education. The use of technology has become a central part of the practice of professional nursing. Graduates of nursing programs today must be able to use IT tools, such as clinical information systems. Saudi nurses must be prepared to utilize these technologies for the advancement of science and nursing practice in local and global communities. Little attention has been directed to students’ attitudes about computer usage in academic communities in Saudi Arabia.